A ruptured abdominal aortic aneurysm was just the tip of the iceberg – A rare case of IgG4-related disease and multiple giant aneurysms - LongHai Jin; Gert Frahm-Jensen (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Immunoglobulin G4-related disease (IgG4-RD) is a rare fibroinflammatory disorder that often presents with multi-organ manifestations. A 65-year-old man was retrieved to our tertiary institution with acute groin pain and severe hypotension. A 12 cm ruptured abdominal aortic aneurysm (AAA) was identified on a computed tomography (CT) aortogram. He underwent an emergency open repair of the AAA. However, this transpired to be just the tip of the iceberg. The CT study also revealed multiple giant iliac and coronary artery aneurysms as well as an obliterative pancreatic lesion. Although the AAA did not exhibit the typical macroscopic features of an inflammatory aneurysm, IgG4-RD was suspected based on the constellation of the affected organs. This diagnosis was initially supported by a raised serum IgG4 level and was later confirmed on histopathology of the resected coronary artery aneurysm. This article highlights IgG4-RD as an important differential diagnosis, despite its novelty, rarity and complexity, especially for atypical presentations of vasculitis and aneurysms.